An improved phase-coding method for absolute phase retrieval based on the path-following algorithm. (November 2019) - Lv, Shenzhen; Sun, Qiang; Yang, Jianbai; Jiang, Yang; Qu, Feng; Wang, Jian
Highlights: An improved method to remove phase unwrapping artifacts of absolute phase retrieval in the phase-coding procedure is proposed when a mass of codewords is required. Computational framework is presented which is with aid of path following algorithm. For tested standard sphere with radius of 15.0053 mm, the radius error of fitted sphere is −0.0699 mm which is much smaller than that by traditional phase-coding method. Compared with other improved phase-coding method, extra fringe patterns are not required by this method. Abstract: Although the traditional phase-coding method for absolute phase retrieval possesses strong robustness, the method leads to unwrapping artifacts as a mass of codewords required. To solve this problem, a novel improved method is proposed in this paper. The incorrect points in the recovered phase via the traditional method are located using a computational framework, and the path-following algorithm is adopted as an aid to correct the unwrapping artifacts. The effectiveness of the proposed method is experimentally verified by an established measurement system. The reconstructed geometry of standard sphere has sufficient accuracy and the absolute phase retrieval of a complex star object has high quality.